Legal Protection Efforts for Workers Through the Social Security Administrative Agency - Angie Angie (CV. Rayyan Dwi Bharata, 2023)
Labor social security (Jamsostek) is a form of protection provided to workers and their families against various labor market risks. Various formal Jamsostek programs that have been running in Indonesia are: (i) for private sector employees, managed by PT Jamsostek; (ii) for civil servants, managed by PT Taspen and PT Askes; and (iii) for TNI and Polri members, managed by PT Asabri. The scope of this program consists of four worker protection programs, namely: (i) work accident insurance; (ii) death guarantee; (iii) old age security; and (iv) health care guarantees. Objectively it will be very difficult to make the Jamsostek program the main mechanism for the social protection system if the management remains as it is now. The monopoly system in the implementation of the Social Security program is an inhibiting factor for the development of the social security system for workers who wish to develop it. Currently, Indonesia needs an integrated national workers' social security system and its implementation is entrusted to private parties who have proven capabilities in this field. In this system, the government plays a more regulatory and supervisory role, and sets minimum standards for various components of social security that must be provided by every employer to their workers.